ATC Mw7.1 Puebla-Morelos earthquake reconnaissance observations: Structural observations and instrumentation. Issue 2 (December 2020) - Lan, Yun Jennifer; Stavridis, Andreas; Kim, Insung; Diaz-Fanas, Guillermo; Heintz, Jon; Hernández-Bassal, Laura; Anzola, Esteban; Berkowitz, Russell; Hussain, Saif; Jalalian, Afshar; Garini, Evangelia; Ktenidou, Olga-Joan; et al.
After the 2017 Puebla-Morelos earthquake, the Applied Technology Council (ATC) funded a mission to Mexico City to collect structural, geotechnical, seismological, and damage information on concrete structures. The collected data set includes 70 reinforced concrete buildings and contains photos, design drawings, ground motion records, ambient vibration data, and reconnaissance observations, where available. This article presents the most important structural observations and instrumentation findings. The data show that, in buildings with a flexible lateral system, the unreinforced masonry infill walls resisted substantial load and prevented more severe damage to the structural system. Many previously retrofitted buildings failed in locally unreinforced areas, because retrofits did not comprehensively strengthen all weaknesses in the building. Significant damage was also observed in buildings with weak story irregularities and buildings founded on weak soil.